The Fed's real reaction function: monetary policy, inflation, unemployment, inequality and presidential politics - James K. Galbraith; Olivier Giovannoni; Ann J. Russo (Levy Economics Institute of Bard College, 2007)
Using a VAR model of the American economy from 1984 to 2003, we find that, contrary to official claims, the Federal Reserve does not target inflation or react to inflation signals. Rather, the Fed reacts to the very real signal sent by unemployment, in a way that suggests that a baseless fear of full employment is a principal force behind monetary policy. Tests of variations in the workings of a Taylor Rule, using dummy variable regressions, on data going back to 1969 suggest that after 1983 the Federal Reserve largely ceased reacting to inflation or high unemployment, but continued to react when unemployment fell too low. Further, we find that monetary policy (measured by the yield curve) has significant causal impact on pay inequalitya domain where the Fed refuses responsibility. Finally, we test whether Federal Reserve policy has exhibited a pattern of partisan bias in presidential election years, with results that suggest the presence of such bias, after controlling for the effects of inflation and unemployment.
Keywords: D31; E24; E31; E43; J31; 330; Personal Income; Wage Level; Wage Differentials; Price Level; Inflation; Deflation; Term Structure of Interest Rates